2021
DOI: 10.1051/e3sconf/202123400041
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral water footprint dynamics: An input-output structural decomposition analysis for Morocco

Abstract: Over the last decades, Morocco has been facing increasingly severe water scarcity. To quantify water use in Morocco, we refer to the water footprint (WF) concept, including both direct and indirect water use. WF considered covers internal WF and exported virtual water (VW). We used the input-output structural decomposition analysis (SDA) to quantitatively analyze the drivers of changes in Morocco’s sectoral WF from 1995 to 2015. The considered mechanisms governing WF changes are the technological, economic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Simbi et al (Simbi et al, 2021) conducted a decomposition and decoupling analysis of Africa's economic growth and carbon dioxide emissions. From 1995 to 2015, Achraf et al (Achraf et al, 2021) utilized input-output structural decomposition analysis (SDA) to evaluate the causes of sectoral water variations in Morocco quantitatively. The findings indicated that the technological effect served as a multiplier, while the economic system efficiency effect aided water conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Simbi et al (Simbi et al, 2021) conducted a decomposition and decoupling analysis of Africa's economic growth and carbon dioxide emissions. From 1995 to 2015, Achraf et al (Achraf et al, 2021) utilized input-output structural decomposition analysis (SDA) to evaluate the causes of sectoral water variations in Morocco quantitatively. The findings indicated that the technological effect served as a multiplier, while the economic system efficiency effect aided water conservation.…”
Section: Introductionmentioning
confidence: 99%